Association of cytochrome P450 genetic polymorphisms with neoadjuvant chemotherapy efficacy in breast cancer patients - Seredina Tatyana A; Goreva Olga B; Talaban Valeria O; Grishanova Alevtina; Lyakhovich Vyacheslav V (BMC, 2012)
Abstract Background The enzymes of the cytochrome P450 family (CYPs) play an important role in the metabolism of a great variety of anticancer agents; therefore, polymorphisms in genes encoding for metabolizing enzymes and drugs transporters can affect drug efficacy and toxicity. Methods The genetic polymorphisms of cytochrome P450 were studied in 395 patients with breast cancer by RLFP analysis. Results Here, we studied the association of functionally significant variant alleles of CYP3A4, CYP3A5, CYP2B6, CYP2C8, CYP2C9 and CYP2C19 with the clinical response to neoadjuvant chemotherapy in breast cancer patients. A significant correlation was observed between the CYP2C9*2 polymorphism and chemotherapy resistance (OR = 4.64; CI 95% = 1.01 - 20.91), as well as between CYP2C9*2 heterozygotes and chemotherapy resistance in women with nodal forms of breast cancer and a cancer hereditary load (OR = 15.50; CI 95% = 1.08 - 826.12) when the potential combined effects were examined. No significant association between chemotherapy resistance and the other examined genotypes and the potential combined clinical and tumour-related parameters were discovered. Conclusion In conclusion, CYP2C9*2 was associated with neoadjuvant chemotherapy resistance (OR = 4.64; CI 95% = 1.01 - 20.91) in the population of interest.